Dual-Action Protein-siRNA Conjugates for Targeted Disruption of CD47-Signal Regulatory Protein α Axis in Cancer Therapy - Lee, Jong Won; Yoon, Hong Yeol; Ko, Young Ji; Kim, Eun Hye; Song, Sukyung; Hue, Seungmi; Gupta, Nilaksh; Malin, Dmitry; Kim, Jay; Kong, Byoungjae; Kim, Sehoon; Kim, In-San; et al. (American Chemical Society, 2024)
A series of successes in RNA interference (RNAi) therapies for liver diseases using lipid nanoparticles and N-acetylgalactosamine have heralded a current era of RNA therapeutics. However, alternative delivery strategies are required to take RNAi out of the comfort zone of hepatocytes. Here we report SIRP alpha IgV/anti-CD47 siRNA (vS-siCD47) conjugates that selectively and persistently disrupt the antiphagocytic CD47/SIRP alpha axis in solid tumors. Conjugation of the SIRP alpha IgV domain protein to siRNAs enables tumor dash through CD47-mediated erythrocyte piggyback, primarily blocking the physical interaction between CD47 on cancer cells and SIRP alpha on phagocytes. After internalization of the vS-siCD47 conjugates within cancer cells, the detached free-standing anti-CD47 siRNAs subsequently attack CD47 through the RNAi mechanism. The dual-action approach of the vS-siCD47 conjugate effectively overcomes the "don't eat me" barrier and stimulates phagocyte-mediated tumor destruction, demonstrating a highly selective and potent CD47-blocking immunotherapy. This delivery strategy, employing IgV domain protein-siRNA conjugates with a dual mode of target suppression, holds promise for expanding RNAi applications beyond hepatocytes and advancing RNAi-based cancer immunotherapies for solid tumors.